F18-FDG PET/CT in a patient with Antisynthetase Syndrome - Nazerani-Zemann, Tina; Stanzel, Susanne; Gstettner, Christian; Aigner, Reingard Maria; Pernthaler, Birgit (Nuklearmedizin - NuclearMedicine, 2023)
More prevalent in women than men, Antisynthetase Syndrome is a rare and poorly defined autoimmune disease associated with interstitial lung disease, polymyositis, and dermatomyositis. In addition to various diagnostic tools, imaging modalities are needed in certain situations. A 42-year-old woman with Anti-Jo-1-positive Antisynthetase Syndrome presented with thoracic muscular pain. She underwent whole-body Fluorodeoxyglucose positron emission tomography/computed tomography (F18-FDG PET/CT) to evaluate the total extent of the muscles affected. Depicting symptomatic symmetric myositis of the intercostal muscles, F18-FDG PET/CT additionally revealed unusually extensive fasciitis of the lower extremities.
Keywords: F18-FDG-PET/CT, Antisynthetase Syndrome, Fasciitis